An evaluation of total starch and starch gelatinization methodologies in pelleted animal feed - Zhu, L.; Jones, Cassandra K.; Guo, Q.; Lewis, L.; Stark, Charles R.; Alavi, Sajid (My University, 2016)
The quantification of total starch content (TS) or degree of starch gelatinization (DG) in animal feed is always challenging because of the potential interference from other ingredients. In this study, the differences in TS or DG measurement in pelleted swine feed due to variations in analytical methodology were quantified. Pelleted swine feed was used to create 6 different diets manufactured with various processing conditions in a 2 x 3 factorial design (2 conditioning temperatures, 77 or 88 degrees C, and 3 conditioning retention times, 15, 30, or 60 s). Samples at each processing stage (cold mash, hot mash, hot pelletized feed, and final cooled pelletized feed) were collected for each of the 6 treatments and analyzed for TS and DG. Two different methodologies were evaluated for TS determination (the AOAC International method 996.11 vs. the modified glucoamylase method) and DG determination (the modified glucoamylase method vs. differential scanning calorimetry [DSC]). For TS determination, the AOAC International method 996.11 measured lower TS values in cold pellets compared with the modified glucoamylase method. The AOAC International method resulted in lower TS in cold mash than cooled pelletized feed, whereas the modified glucoamylase method showed no significant differences in TS content before or after pelleting. For DG, the modified glucoamylase method demonstrated increased DG with each processing step. Furthermore, increasing the conditioning temperature and time resulted in a greater DG when evaluated by the modified glucoamylase method. However, results demonstrated that DSC is not suitable as a quantitative tool for determining DG in multicomponent animal feeds due to interferences from nonstarch transformations, such as protein denaturation.
Citation: Zhu, L., Jones, C., Guo, Q., Lewis, L., Stark, C. R., & Alavi, S. (2016). An evaluation of total starch and starch gelatinization methodologies in pelleted animal feed. Journal of Animal Science, 94(4), 1501-1507. doi:10.2527/jas2015-9822
Keywords: Analytical Methods; Animal Feed; Degree Of Gelatinization; Total Starch; Metabolizable Energy; Diets